PELATIHAN EKONOMI DAN KEUANGAN SYARIAH DALAM RANGKA PEMBENTUKAN BAITUL MAL WAT TAMWIL - Herianingrum, Sri; Cahyono, Eko Fajar; Rani, Lina Nugraha; Rusmita, Sylva Alif (Studi Kasus Inovasi Ekonomi, 2019)
The background of this activity was to fulfill the aspirations of the Muslims of Bandar Kidul village, Mojoroto Subdistrict, Kediri City to carry out economic activities following Islamic rules and the potential capabilities and skills possessed by management and members of the Fascho cooperative to manage Islamic microfinance institutions such as Baitul Wat Tamwil . The purpose of this community service activity is to provide understanding, knowledge, and skills to the management and members of the Fascho cooperative who are engaged in Mojoroto Subdistrict, Kediri City about Islamic economics and Islamic Finance. The activity took place in May 2018, and the actions were in the form of workshop and socialization about Islamic economics and Islamic finance. The article is expected to be a provision for administrators and members to establish Baitulmal wat Tamwil. The results of the activities were in the form of increased awareness of the community around the location of the community service and the increased knowledge and skills of the members and administrators of the Fascho Cooperative so that they were better prepared to establish the BMT.